Chagas' disease and social security: a case-control study in an urban area, Goiás, Brazil Doença de Chagas e previdência social: estudo caso-controle em uma área urbana, Goiás, Brasil - Fábio Zicker (Universidade de São Paulo, 1988)
One hundred and twenty subjects with Chagas' cardiopathy and 120 non-infected subjects were randomly selected from first time claimants of sickness benefits in the National Institute of Social Security (INPS) in Goiás. Cases of Chagas' cardiopathy were defined based on serological test, history of residence in an endemic area and, clinical and/or electrocardiogram (ECG) alterations suggestive of Chagas' cardiomyopathy. Controls were defined as subjects with at least two negative serological tests. Case and controls were compared in the analysis for age, sex, place of birth, migration history, socio-economic level, occupation, physical exertion at work, age at affiliation and years of contribution to the social security scheme, clinical course of their disease and ECG abnormalities. Chagas' disease patients were younger than other subjects and predominantly of rural origin. Non-infected subjects presented a better socio-economic level, were performing more skilled activities and had less changes of job than cases. No important difference was observed in relation to age at affiliation to INPS. About 60% of cases have claimed for benefits within the first four years of contribution while among controls this proportion was 38.5%. Cases were involved, proportionally more than controls, in "heavy" activities. A risk of 2.3 (95%CL 1.5 - 4.6) and 1.8 (95%CL 1.2- 3.5) was obtained comparing respectively "heavy" and "moderate" physical activity against "light". A relative risk of 8.5 (95%CL 4.9 - 14.8) associated with the presence of cardiopathy was estimated comparing the initial sample of seropositive subjects and controls. A high relative risk was observed in relation to right bundle branch block (RR = 37.1 95%CL = 8.8 - 155.6) and left anterior hemiblock (RR = 4.4, 95%CL = 2.1 - 9.1). São descritas as características sociais e ocupacionais de um grupo de pacientes chagásicos em área urbana no intuito de se estudar a importância médico-social da doença de chagas como causa de incapacidade laborativa. Cento e vinte pacientes portadores de cardiopatia chagásica e 120 pacientes controles, não infectados pelo Trypanosoma cruzi, foram selecionados ao acaso entre os requerentes de auxílio doença-previdenciário no Instituto Nacional de Previdência Social (INPS) de Goiás (Brasil). Os dois grupos foram comparados em relação a idade, sexo, local de nascimento, história de migração, nível sócio-econômico, esforço físico no trabalho, idade de filiação e anos de contribuição ao INPS, evolução clínica e presença de alterações eletrocardiográficas. Verificou-se que os indivíduos chagásicos apresentavam nível sócio-econômico mais baixo, desenvolviam atividades profissionais de menor especialização e recorreriam à previdência social para benefícios por incapacidade em idade mais jovem e com menor tempo de contribuição quando comparados ao grupo controle. O esforço físico ocupacional estava associado a um risco relativo de 2,3 (LC95% 1,5-4,6) e 1,8 (LC95% 1,2-3,5) comparando-se, respectivamente, atividades físicas ''pesada" e "moderada" em relação a atividades ocupacionais "leves". Comparando-se a amostra inicial de soropositivos e soronegativos (controles), foi estimado um risco relativo associado à cardiopatia de 8,5 (LC95% 4,9-14,8). Riscos relativos de 37,1 (8,8 - 155,6) e 4,4 (2,1 - 9,1) foram obtidos para o bloqueio de ramo direito e hemibloqueio anterior esquerdo, respectivamente.